Analysis Of The Influence Of Human Resource Competency, Price, And Hospital Image On Patient Satisfaction In General, That Impact Patient Loyalty At Karya Husada Hospital - Irza Haicha Pratama; Ali Napiah Nasution; Nathasya Nainggolan (CV. Inara, 2025)
To increase patient satisfaction and loyalty, not only are superior human resource competence and prices appropriate to the health services provided to patients needed, but the hospital image also influences patient satisfaction and loyalty. This research aims to analyze the influence of human resource competence, price, and hospital image on general patient satisfaction, which impacts loyalty at Karya Husada Hospital. The type of research used is analytical, quantitative research. The sample used in this study was 200 patients, and the analysis used was univariate, bivariate, and multivariate. The research results showed that most patients felt satisfied with the human resources, prices, and image of Karya Husada Hospital—as many as 178 (89%), and the majority of patients felt loyal to Karya Husada Hospital, as many as 184 (92%). There is an influence of human resource competency on general patient satisfaction at Karya Husada Hospital, there is an influence of price on general patient satisfaction at Karya Husada Hospital, there is an influence of hospital image on general patient satisfaction at Karya Husada Hospital, there is an influence of human resource competency on general patient loyalty at Karya Husada Hospital, there is an influence of price on the loyalty of general patients at Karya Husada Hospital, there is an influence of hospital image on the loyalty of general patients at Karya Husada Hospital. The variable that most influences patient satisfaction is the price variable (X2). The variable that most influences patient loyalty is the hospital image variable (X3).